Investigation on Behavior of Castellated Composite Beams under Fire - Wang Yuhan; Jia Lianguang; Li Xuefeng (MATEC Web of Conferences, 2018)
This paper is to study the fire resistance of castellated composite beams. Based on experiment, a reasonable castellated composite beam model is established by using finite element software. The critical temperature of castellated composite beams influenced by hole opening ratio, hole pitch, width-thickness ratio of the web and stiffener have been analyzed. The result shows that stiffener has a great influence on the fire resistance of castellated composite beams, which can increase the critical temperature greatly. The width-thickness ratio of the web has some influence on the buckling behavior of castellated composite beams under fire condition. When width-thickness ratio is higher, the web is more prone to buckling failure. The hole opening ratio and hole pitch have a little influence on the fire resistance of castellated composite beams.